Dampak Perkembangan Teknologi Informasi, Pengalaman, dan Kemampuan terhadap Prestasi Karyawan - Romadhoni, Khoirul; Herawati, Jajuk (Jurnal Ilmiah Manajemen Kesatuan, 2021)
The research titled Impact of Information Technology Development, Experience, and Capability on Employee Achievement of The Department of Agriculture and Food Security has the aim to prove that employee achievement is influenced by several factors such as those contained in this research, namely the development of information technology, experience, and ability. And also other factors that were not included in this study. Of the 102 employees who were respondents to this study, the four hypotheses of this study were accepted. From simple regression testing, it was concluded that partial development of information technology, experience, and ability has a positive and significant influence on the achievements of employees in the Department of Agriculture and Food Security of the Special Region of Yogyakarta. ANOVA testing also produced findings that simultaneously or jointly the development of information technology, experience, and ability to influence the achievements of employees in the Department of Agriculture and Food Security of the Special Region of Yogyakarta.